DEVELOPMENT OF QUALITY STEEL ALLOY LIQUIDATION TECHNOLOGY - Saidmakhamadov Nosir; Turakhodjaev Nodir; Abdullaev Kamol; Kholmirzaev Nozimjon; Tadjiev Nuritdin (Journals Park Publishing, 2022)
In this article, the mode of liquefaction of 35XGCL steel alloy was used. The obtained liquid metal is cleaned from non – metallic inclusions and gas pores by non – furnace processing, and casting technology was developed on the basis of energy and resource efficient innovative technologies. The composition of the sand – clay mold was worked out to obtain a high – quality cast product, and a high – quality cast product was obtained by liquefaction. Also, thermal treatment regimes were developed to increase the mechanical properties of the cast alloy, and as a result, a high – quality and resource – efficient cast product was obtained.
Keywords: chrome, manganese, alloyed, shaft, sand – clay mold